Incidence of extramedullary disease in patients with acute promyelocytic leukemia: a single-institution experience - Vega-Ruiz, Arturo (2009)
Using current treatment regimens, over 90% of patients with acute promyelocytic leukemia will achieve complete remission (CR). However, approximately 30% of these patients will relapse, including a small proportion who will develop extramedullary disease (EMD). In this study, we investigated the incidence of EMD in 263 patients with APL who were treated at our institution from January 1990 to May 2008. With a median follow-up of 31 months (range 2 days–203 months), 8 (3%) patients developed EMD. The most commonly affected site was the central nervous system (n = 7). Before developing EMD, one patient had achieved CR with a chemotherapy-only regimen, six patients had achieved CR with all-trans-retinoic acid (ATRA)-based regimens, and one patient had achieved CR with an ATRA plus arsenic trioxide (ATO)-based regimen. The EMD conferred a poor prognosis; five patients died within 4 months of developing EMD. The molecular status did not predict EMD; four patients had a negative PCR for the PML-RARA transcripts prior to relapse with EMD. In conclusion, the incidence of EMD is low. We were unable to identify any specific factors that could predict the development of EMD.